Μελέτη της συσχέτισης πολυμορφισμών του γονιδίου της προλακτίνης στη γαλακτοπαραγωγή του χιώτικου προβάτου - Xριστοδουλίδου, Ιωάννα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
In recent years, the research around the genes affecting reproductive characteristics of sheep has been of major interest. In Cyprus, the Chios breed is mainly used for the production of sheep milk. An important gene responsible for the synthesis and secretion of milk is prolactin which is believed to affect the quality and quantity of milk produced and its components (such as protein and fat composition). Several polymorphisms have been found to affect milk production by either increasing or decreasing the milk components. This study aims to assess the presence of single nucleotide polymorphisms (SNPs) in exon 3 of prolactin gene and to investigate possible association of them with milk production and fat composition. For this purpose, 106 DNA samples from Chios sheep were collected. The presence of the alleles A/C and A/G were examined in the SNP 1 and SNP 2 respectively by the use of PCR and sequencing of the samples. The results indicated that there is a relation between the genotypes CC/CA of SNP 1 and milk production and the genotypes CA/AA and the percentage of fat. The remaining genotypes of SNP 1 and all the genotypes of SNP 2 were not associated with milk production or fat composition.
Keywords: Genes; Sheeps; Γονίδια; Πρόβατα